PENGARUH KONDISI EKONOMI ORANG TUA TERHADAP MOTIVASI MELANJUTKAN PENDIDIKAN SISWA MADRASAH ALIYAH AL-ANWAR PONTIANAK - Hidayah, Nurul; Aminuyati, Aminuyati; Achmadi, Achmadi (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstractThe aims of study is to determine the effect of parent’s economic conditions to continue their education to college students of class XII IPS MA Al-Anwar Pontianak. The method is descriptive method. The population were the student’s class XII IPS MA AL ANWAR Pontianak totaling 65 students. The data collecting is used technique of direct communication, indirect communication techniques and documentary studies. The data analyze is using SPSS version 18.0. Then, data analysis that states there is influence between the economic condition of parents against the motivation of continuing education to college amounted to 11,4% with a coefficient of determination equal to 0,338(R) with R Square 0,114 low level of relationship interpretation.Keywords: Economic Condition, Parent, Motivation